2006
DOI: 10.1063/1.2358710
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-top atomic force microscope

Abstract: We present the implementation of an atomic force microscope ͑AFM͒ based on fiber-top design. Our results demonstrate that the performances of fiber-top AFMs in contact mode are comparable to those of similar commercially available instruments. Our device thus represents an interesting alternative to existing AFMs, particularly for applications outside specialized research laboratories, where a compact, user-friendly, and versatile tool might often be preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 16 publications
2
43
0
Order By: Relevance
“…From the signal of the readout system, it is thus possible to remotely sense mechanical displacements of the ferrule-top device. 9,10,12,13 It is to note that the fabrication procedure presented here is slightly different with respect to that described in Refs. 12 and 13.…”
Section: Ferrule-top Probe: Fabrication and Readoutmentioning
confidence: 97%
See 1 more Smart Citation
“…From the signal of the readout system, it is thus possible to remotely sense mechanical displacements of the ferrule-top device. 9,10,12,13 It is to note that the fabrication procedure presented here is slightly different with respect to that described in Refs. 12 and 13.…”
Section: Ferrule-top Probe: Fabrication and Readoutmentioning
confidence: 97%
“…In 2006, our group has proposed a new generation of miniaturized devices that may solve this issue: the fiber-top cantilever. 9,10 In a fiber-top probe, the cantilever is carved at the center of the cleaved end of an optical fiber. Light coupled from the opposite side of the fiber can then be used to detect the deflection of the cantilever.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that these devices can be used as optomechanical transducers 1,2-4 , temperature sensors 1 , hydrogen sensors 5 , and atomic force microscopes 6 . For further details, we refer the reader to our original papers.…”
Section: Fiber-top Cantilevers: Sensors On the Tip Of A Fibermentioning
confidence: 99%
“…Fiber-top cantilevers have been proven to provide a new platform for several applications, including gas sensing, 2 refractive index measurements, 3 and atomic force microscopy. 4 Unfortunately, fiber-top cantilevers are currently fabricated by means of a time consuming process that does not adapt well to series production (namely, focused ion beam milling 5 ). This problem was solved at the beginning of 2010 by introducing a larger (but still compact and monolithic) device that retains the advantages of fiber-top technology without the burden of the fabrication costs: the ferrule-top cantilever.…”
Section: A)mentioning
confidence: 99%